Price Adjustment at Multiproduct Retailers - Daniel Levy; Shantanu Dutta; Mark Bergen; Robert Venable (Managerial and Decision Economics, 1998)
We empirically study the price adjustment process at multiproduct retail stores. We use a unique store level data set for five large supermarket and one drugstore chains in the USA, to document the exact process required to change prices. Our data set allows us to study this process in great detail, describing the exact procedure, stages, and steps undertaken during the price change process. We also discuss various aspects of the microeconomic environment in which the price adjustment decisions are made, factors affecting the price adjustment decisions, and firm-level implications of price adjustment decisions. Specifically, we examine the effects of the complexity of the price change process on the stores' pricing strategy. We also study how the steps involved in the price change process, combined with the laws governing the retail price setting and adjustment, along with the competitive market structure of the retail grocery industry, influence the frequency of price changes. We also examine how the mistakes that occur in the price change process influence the actions taken by these multiproduct retailers. In particular, we study how these mistakes can make the stores vulnerable to civil law suits and penalties, and also damage their reputation. We also show how the mistakes can lead to stockouts or unwanted inventory accumulations. Finally, we discuss how retail stores try to minimize these negative effects of the price change mistakes.
Keywords: E31; E12; E50; G13; G14; L11; L15; L16; M21; M31; Q11; Q13; 330; Cost of Price Adjustment; Price Adjustment Process; Menu Cost; Posted Prices; Multiproduct Retailer; Price Rigidity; Sticky Prices; Frequency of Price Changes; Time Dependent Pricing; Retail Supermarket and Drugstore Chains